Establishment of a model of acetaminophen-induced hepatotoxicity in different weekly-aged ICR mice. (October 2015) - Taguchi, K; Tokuno, M; Yamasaki, K; Kadowaki, D; Seo, H; Otagiri, M
Acetaminophen (APAP), a widely used analgesic and antipyretic drug, has the potential to cause lethal hepatotoxicity. Mice are widely used for developing murine models of APAP-induced hepatotoxicity, and many researchers have used these models for APAP-related studies including the fields of biology, pharmacology and toxicology. Although drug-induced hepatotoxicity is dependent on a number of factors (species, gender and age), very few studies have investigated the effect of aging on APAP hepatotoxicity. In this study, we evaluated the effect of age on APAP-induced hepatotoxicity in different weekly-aged mice to establish a model of APAP-induced hepatotoxicity that is an accurate reflection of general experimental conditions. Male ICR mice 4, 6, 8, 10 and 12 weeks old were given APAP intraperitoneally, and mortality, hepatic damage and the plasma concentration of APAP metabolites were evaluated. It was found that younger male ICR mice were relatively resistant to hepatotoxicity induced by intraperitoneal APAP administration. In addition, the APAP-glucuronide concentration in plasma remained essentially the same among the differently-aged mice, while APAP-sulfate levels were dramatically decreased in an age-dependent manner. Thus, it is recommended that mice of the same ages be used in studies related to APAP-induced hepatotoxixity. These results provide evidence in support of not only the age-related changes in susceptibility to APAP-derived hepatotoxicity in mice but also in developing mouse models for APAP-related studies.